DEVELOPMENT OF MATHEMATICS LEARNING DEVICES WITH PROBLEM BASED LEARNING MODEL ON SET MATERIAL FOR THE SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Zahratul Maika; Rini Dian Anggraini; Syofni (Jurnal Prinsip Pendidikan Matematika, 2021)
The background of this research is the existence of curriculum change that claiming teachers to develop the learning devices and also still the limited learning devices that matching with the 2013 curriculum. This research aims to produce products in the form of mathematics learning devices such as syllabus, lesson plan, and student worksheet. The research method in this research is research and development. The development model in this research is the 4-D model which consists of the following stages define, design, develop and disseminate. The learning devices have been validated by three validators. Based on the analysis, the result of the validation of syllabus, lesson plan, and student worksheet is 3,73; 3,59; and 3,52 with very valid categories. The student worksheet that has been valid then tried out to the small groups (6 students) with different cognitive abilities. In the current conditions of the Covid-19 pandemic, the trial was carried out by sending a student worksheet and questionnaire via WhatsApp. Based on the analysis, the score of the small group trial result of the student worksheet is 3,42 in the very practical category. This research produced mathematics learning devices. Based on analysis and discussion that the of mathematics learning devices such as syllabus, lesson plan and student worksheet with Problem Based Learning model on set material for the seventh grade of junior high school has fulfilled valid category and student worksheet has fulfilled practical category.